Safeguarding Pilgrims from Fraud and Organizer Failures: An Islamic Law Analysis of Consumer Protection in Indonesia’s Hajj and Umrah Industry - Abdillah, Abdillah; Ahmad, Ahmad; Jannah, Raodhatul; Anugra, Novia (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2026)
Fraud and organizational failures in Indonesia’s Hajj and Umrah industry have surged alongside rapid sectoral growth, inflicting significant financial, emotional, and spiritual losses on pilgrims. These malpractices consistently violate core principles of fiqh muamalah, particularly the wakalah (agency) contract and amanah (trustworthiness), while incorporating prohibited elements of gharar (excessive uncertainty) and ghishsh (deceit). Employing a normative juridical approach, this study utilizes library-based data collection from primary sources (Al-Qur’an, authentic Hadith collections, classical fiqh texts across the four madhhabs, contemporary fatwas from MUI and DSN-MUI, and key legislation including Law No. 14 of 2025 and Law No. 8 of 1999) and secondary sources (scholarly works and reports published 2021-2026). Data were analyzed through deductive qualitative content analysis comparing Islamic transactional principles with Indonesian positive law provisions. Findings reveal persistent ethical breaches in recent 2025–2026 cases such as PT NMA’s failure to depart over 1,000 Haji Furoda pilgrims, embezzlement exceeding Rp 1 billion in Ternate, and fraudulent Umrah packages by operators in Lampung Utara and Samarinda demonstrating patterns of fund misappropriation, counterfeit visas, and unilateral cancellations. While legal safeguards under Law No. 14 of 2025 and Law No. 8 of 1999 are robust (including mandatory licensing, escrow accounts, and digital monitoring), implementation challenges persist, notably in proactive enforcement and cross-jurisdictional coordination. This study pioneeringly offers the first comprehensive post-2025 regulatory analysis integrating maqasid al-syariahh particularly Hifzu al-Mal into national frameworks, proposing a novel set of actionable strategies (maqasid-based licensing assessments, institutional synergy with DSN-MUI, blockchain-enhanced transparency, and fiqh-integrated arbitration) to shift enforcement toward preventive, transparent, and restorative justice models. These contributions bridge fiqh muamalah with contemporary Indonesian law, providing policymakers with practical tools to enhance accountability and align pilgrimage services with religious and public welfare goals.